Practices and progress in farmer participatory research in China - Huang, Jie; Li, Kaimian; Zhang, Weite; Lin, Xiong; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2001)
The FPR project in China is a cooperative project between CIAT and CATAS, and is financially supported by the Nippon Foundation of Japan. This paper mainly describes results of the FPR trials conducted in Hainan province of China and discusses the function of FPR in the transfer of cassava technologies, existing problems and future development prospects. The project involves the following aspects of research: variety trials, soil and water conservation and fertilizer management. Contour barriers of tropical grass and legume species, and intercropping with peanut and other legume crops have been shown to be effective in protecting the soil from erosion. Results based on trials conducted at CATAS from 1995 to 1999 indicate that hedgerows of vetiver grass, Clitoria ternatea, Chamaecrista rotundifolia, Indigofera endecaphylla, Arachis pintoi, Tephrosia candida, Ananas comosus and Brachiaria decumbens decreased dry soil loss (5-30 t/ha) by 65-94%, compared to the check treatment which had a dry soil loss of 85 t/ha. FPR trials conducted by farmers in their own fields indicate that cassava intercropped with peanut and planting vetiver grass as contour barriers was the best practice: dry soil loss decreased by 28-57% compared to the check treatment, and increased income by 3,300 Yuan/ha. This practice has been widely adopted by farmers in the pilot site of Kongba village in Baisha county of Hainan, and is being disseminated to neighboring villages by farmer-to-farmer extension. During 1995-1999, more than 41 promising clones have been tested in 38 farmers’ fields; they were harvested and evaluated by farmers themselves. Results show that SC8013 and OMR33- 10-4 outyielded the check variety SC205 by 13.1% and 34.4%, respectively. However, there were no significant differences among varieties in terms of soil erosion control. It is very easy for farmers to select and adopt their favorate varieties through their own participation. This approach will enhance the dissemination of new varieties and technologies. Fertilizer trials were conducted in 14 farmers’ fields using 12 treatments. The results show that all the treatments with fertilizers produced higher yields than those without fertilizers, and that application of 300 kg/ha of a special fertilizer (No. 3) increased the yield by 33% and gross income by 22%. This result will help convince farmers to apply fertilizers to their cassava fields in the future.